The Tea Plant Leaf Cuticle: From Plant Protection to Tea Quality - Chen, Mingjie (Frontiers in Plant Science, 2021)
Camellia sinensis (tea tree) is a perennial evergreen woody crop and has been planted in more than 50 countries worldwide; its leaves are harvested to make tea which is one of the most popular non-alcoholic beverages. Cuticle is the major transpiration barrier to restrict nonstomatal water loss, and affects the drought tolerance of tea plants. Cuticle may also provide molecular cues for the interaction with herbivores and pathogens. The tea making process almost always includes a postharvest withering treatment to reduce leaf water content, many studies have demonstrated that withering treatment-induced metabolite transformation is essential to shape the quality of made tea. Tea leaf cuticle is expected to affect its withering properties and the dynamic of metabolome remodeling. In addition, it has long been speculated that cuticle may contribute to the aroma quality of tea. However, concrete experimental evidence is lacking to prove or disprove this hypothesis. Even though its relevance to the abiotic and biotic stress tolerance and postharvest processing properties, tea cuticle has long been neglected. Recently, there are several studies on tea cuticle regarding its structure, wax composition, transpiration barrier organization, environmental stresses-induced wax modification, and structure-function relations. This review is devoted to tea cuticle, the recent research progresses were summarized; unresolved questions and future research directions were also discussed.